Changes of gut microbiota during silybin‐mediated treatment of high‐fat diet‐induced non‐alcoholic fatty liver disease in mice. Issue 1 (5th January 2020) - Li, Xiuxia; Wang, Yanping; Xing, Yilan; Xing, Renxin; Liu, Yongsheng; Xu, Yinsheng
Abstract : Aim: Gut microbiota are involved in the pathogenesis of non‐alcoholic fatty liver disease (NAFLD). Silybin (Sil), a naturally occurring hepatoprotective agent, is widely used for treating NAFLD. Whether Sil affects gut microbiota during its actions in treating NAFLD is unknown. We aimed to examine the effect of Sil on intestinal flora dysbiosis induced by a high‐fat diet (HFD). Methods: After 10 weeks of feeding normal chow diet or HFD, mice were given a daily gavage for 8 weeks. Cecal contents were harvested for study of short‐chain fatty acids, bile acids, and gut microbiota alteration. Results: Sil showed protective effects against dietary‐induced obesity and liver steatosis; accordingly, gut microbiota composition changed. At the phylum level, compared with the HFD group, mice in the Sil‐treated group had significantly lower levels of Firmicutes, and the ratio of Firmicutes‐to‐Bacteroidetes was lower ( P < 0.05). At the genus level, the Sil‐treated group have significantly lower levels of Lachnoclostridium, Lachnospiraceae_UCG‐006, and Mollicutes_RF9, which were reported to be potentially related to diet‐induced obesity, and increased levels of Blautia ( P < 0.05), Akkermansia ( P < 0.05), and Bacteroides ( P < 0.05), which are known to have a beneficial effect on improving NAFLD. Sil also showed an inhibitory effect on well‐known beneficial bacteria, such as Alloprevotella and Lactobacillus . Furthermore, the production of acetate, propionate, and butyrate increased, whereas the generation of formate and conversion of cytotoxic secondary metabolites (lithocholic acid and deoxy‐cholic acid) decreased in mice treated with Sil. Conclusions: Sil might have beneficial effects on ameliorating NAFLD and mediating HFD‐induced change of gut microbiota composition, followed by major changes in secondary metabolites, such as short‐chain fatty acids and bile acids.